Catalase‐Modified Carbon Electrodes: Persuading Oxygen To Accept Four Electrons Rather Than Two. Issue 17 (22nd March 2016) - Sepunaru, Lior; Laborda, Eduardo; Compton, Richard G.
Abstract: We successfully exploited the natural highly efficient activity of an enzyme (catalase) together with carbon electrodes to produce a hybrid electrode for oxygen reduction, very appropriate for energy transformation. Carbon electrodes, in principle, are cheap but poor oxygen reduction materials, because only two‐electron reduction of oxygen occurs at low potentials, whereas four‐electron reduction is key for energy‐transformation technology. With the immobilization of catalase on the surface, the hydrogen peroxide produced electrochemically is decomposed back to oxygen by the enzyme; the enzyme natural activity on the surface regenerates oxygen, which is further reduced by the carbon electrode with no direct electron transfer between the enzyme and the electrode. Near full four‐electron reduction of oxygen is realised on a carbon electrode, which is modified with ease by a commercially available enzyme. The value of such enzyme‐modified electrode for energy‐transformation devices is evident. Abstract : Enzyme electrochemistry : The natural highly efficient activity of an enzyme (catalase) together with carbon electrodes was successfully exploited to produce a hybrid electrode for oxygen reduction, very appropriate for energy transformation (see figure).